Two Ears Are Not Always Better than One: Mandatory Vowel Fusion Across Spectrally Mismatched Ears in Hearing-Impaired Listeners - Reiss, Lina A. J. (J Assoc Res Otolaryngol, 2016)
Hearing loss and auditory prostheses can alter auditory processing by inducing large pitch mismatches and broad pitch fusion between the two ears. Similar to integration of incongruent inputs in other sensory modalities, the mismatched, fused pitches are often averaged across ears for simple stimuli. Here, we measured parallel effects on complex stimulus integration using a new technique based on vowel classification in five bilateral hearing aid users and eight bimodal cochlear implant users. Continua between five pairs of synthetic vowels were created by varying the first formant spectral peak while keeping the second formant constant. Comparison of binaural and monaural vowel classification functions for each vowel pair continuum enabled visualization of the following frequency-dependent integration trends: (1) similar monaural and binaural functions, (2) ear dominance, (3) binaural averaging, and (4) binaural interference. Hearing aid users showed all trends, while bimodal cochlear implant users showed mostly ear dominance or interference. Interaural pitch mismatches, frequency ranges of binaural pitch fusion, and the relative weightings of pitch averaging across ears were also measured using tone and/or electrode stimulation. The presence of both large interaural pitch mismatches and broad pitch fusion was not sufficient to predict vowel integration trends such as binaural averaging or interference. The way that pitch averaging was weighted between ears also appears to be important for determining binaural vowel integration trends. Abnormally broad spectral fusion and the associated phoneme fusion across mismatched ears may underlie binaural speech perception interference observed in hearing aid and cochlear implant users. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s10162-016-0570-z) contains supplementary material, which is available to authorized users.